Konsep Kenabian menurut Ibnu Khaldun (Telaah Korelasi Kemaksuman dan Kemanusiaan Nabi Muhammad SAW) - Munawir Munawir (IAIN Purwokerto, 2014)
Abstract: The results of this study found that Ibn Khaldun divides the soul intothree tiers. The first level is the common man, the soul remains bound by merephysical experience of body organs. The second level, the soul seekers of God, thesoul can rise above physical attachment to a limited degree. The third level is thesoul of the prophet. The prophets are individuals within them God has provided anatural ability to be able to release its humanitarian dimension. This capacity couldchange all of humanity and human spirituality into the highest level of angelic, sothat they can learn all things there without the help of a physical body organs. Thenthey bring back what they have learned it to the level of ability of human understanding,because then that knowledge can be taught to humans. These events were latercalled